PERAN MODAL SOSIAL, POTENSI PARIWISATA DAN PEMBERDAYAAN MASYARAKAT PADA PEMBANGUNAN PARIWISATA BERBASIS MASYARAKAT DI KAWASAN STRATEGIS PARIWISATA LEBIH - Ngurah, I Dewa Gede; Utama, Made Suyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
The main goal of development reduces the gap in society, the main challenge of development in our time is the challenge of inclusion. The concept of development for Bali should be adapted to the potential and conditions of Bali itself, always looking closely at the changing gaps that occur all the time. The tourism sector is a potential development to develop. The tourism sector in Bali province is the income-generating sector. The development of tourism sector in Bali spread throughout the district / city, one of which is Gianyar regency. Development of development in tourism sector should be done continuously (sustainable) by utilizing local community as a manager, so as not to shift the tourism paradigm in areas rich in customs, natural potential (rice fields, mountains and sea).                Analytical technique used is the analysis of structural equations with alternative Partial Least Square (PLS). The result of research shows that the R Square coefficient value of 0.685 means that 68.5 percent of the variation in the quality of Community Based Tourism can be explained by the variation of the quality of social capital, tourism potential, and community empowerment, while the rest of 31.5 percent is explained by other variables not included in the model. Social capital, empowerment and tourism potential has a positive and significant impact on the quality of Community Based Tourism (CBT). The empowerment variable moderate the influence of social capital and tourism potential to community based tourism (CBT) in Gianyar, Sukawati and Blahbatuh Subdistricts.